“Efectos adversos asociados al uso de métodos anticonceptivos en adolescentes de 13 a 19 años que acuden a la consulta obstétrica, Centro De Salud El Mamey- Babahoyo octubre 2018-abril 2019. ¨ - Bayas Peña, Mariuxi del Rosario (2019)
The research, whose result supports this scientific work, includes the study of the adverse effects associated with the use of contraceptive methods; To support the development of the planned work, 234 adolescents between 13 and 19 years of age were selected, who attended the obstetric clinic of the Mamey Health Center, Babahoyo, carrying out the research activity between the month of October 2018 and April 2019, Prefixing as a goal to reach the determination of the adverse effects caused by the use of contraceptive methods in the aforementioned adolescents. The fulfillment of the programmed objectives, demanded the selection of methods of the theoretical level and the empirical level of scientific research, as well as mathematical and statistical methods. The programmed research activity was developed in two stages; in the first, it was possible to diagnose the effects classified as adverse associated to the use of contraceptive methods, in the second a system of promotional and educational actions was elaborated aimed at guaranteeing an adequate preparation of the adolescents object of study regarding the use of contraceptive methods and their adverse effects; which was evaluated by five doctors and the same number of psychologists, with more than 15 years of experience. In the research whose scientific product supported the writing of this thesis, results were reached that, according to the opinion of the specialists consulted, could modify the preparation of young people with respect to the selection and use of contraceptive methods, arriving at conclusions of significant scientific and methodological value .